Eloquence Assemblage in Andalusian Poetry (Journal of the College of Education for Women, 2019)
The eloquence assemblage, as it is appeared in this research, is the most prominent terms thataccompany the art. It includes the whole artworkand it does not stop at the borders of theconstruction, but also extends to the material presented in this or that work. It means thediscovery of all that essential in the material presented and it is far away from what isaccidental and fleeting. Moreover, it is the type of pressure of the poetic status and thefamiliarity with the material flowing subconsciously. It means that the clever poet masters hislanguage alongside with his discernment and intelligence framed by fast-witted. The semanticassemblage within the technical construction means focusing on what embodies that materialand it suggests it and expresses it and gets rid of everything that is redundant, such as extraexplanation and details and every thing that has relationship with disability of the art workeffectiveness. The eloquence assemblage includes the technical image as the image is a spatialand temporal forms that includes a brief process where no place but for the essentials torepresent a distinct and unique linguistic and stylistics economic. The eloquence assemblagemakes the text opened to interpretation, especially when it becomes a source for themysterious and suggested symbols and signs assemblaged within the framework of thetechnical picture and what metaphor, allegory and simile it has and it plays an important rolein enriching the semantic meaning. In fact this depends on the poet's ability and the speed ofhis picking all that is striking and influential and summarizes his artistic work in the overallequation similar to the chemical equation. The researcher discusses the eloquence assemblagein several axes and as followings:- words assemblage linguistically and idiomatically- pressure of words and its semantic interpretation- Mystery and its suggestive connotations- Clarity and its creative and technical connotations- eloquence mobilization and its artistic continuous.At the end, the research puts a list of references and sources and the abstract in English.